Dominican Republic - Poverty Assessment : Poverty in a High-Growth Economy, 1986-2000, Volume 2. Background Papers - World Bank (Washington, DC, 2013)
Since its recovery of macroeconomic stability in 1991, the Dominican Republic has experienced a period of notable economic growth. Poverty has declined in the 1990s. Nevertheless, a segment of the population-mainly in rural areas-does not seem to have benefited from this growth. Poverty in this country in 1998 is less than that of other countries if one adjusts for the level of economic development. The principal poverty characteristics are the following: Disparity in poverty levels in rural areas relative to the rest of the country. Destitution in the "bateyes," the communities arising near the sugar cane plantations, that are mainly composed of women, children, and the aged. Urban vulnerability to environmental problems while access to basic services is restricted. Vulnerability to natural disasters that destroy the means of production. Poverty is high among children--especially those who have abandoned formal education-female-headed households, and the aged-the latter due to lack of social safety nets and the absence of pension systems. There is a strong correlation between poverty and health indicators like the presence of malnutrition, and poverty and education, and poverty and the absence of basic services. Government transfers and foreign remittances play an important role in reducing poverty.